2013
DOI: 10.4236/aa.2013.34026
|View full text |Cite
|
Sign up to set email alerts
|

Angular Photogrammetric Analysis of the Facial Profile of the Adult Bangladeshi Garo

Abstract: The analysis of facial soft tissue from the photographic records gives information about the standard normative values of different facial parameters of a specific population group, helps in the diagnosis of any abnormalities of face and also helps for the treatment plan of patients undergoing orthodontic treatment or facial plastic surgery. The aim of the present study was to measure some craniofacial angles of the Bangladeshi Garo males and females on standardized facial profile photographs and compare them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 12 publications
2
16
4
Order By: Relevance
“…• in men), without surgery (17). After that, our results is closest to Dua et al study in 2010 (32), (96.1 ± 9.1).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…• in men), without surgery (17). After that, our results is closest to Dua et al study in 2010 (32), (96.1 ± 9.1).…”
Section: Discussionsupporting
confidence: 78%
“…From this perspective, preoperative angle in this study is closest to Garo's study (17), Average ideal angle was from this perspective, in this study, preoperative angle in men (90-100…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Consistent with our study, Ferdousi et al found no statistically significant gender differences in the nasolabial angle.Furthermore, we found that the average angle of facial convexity in this study (female subjects = 169.26 ± 4.43 degrees; male subjects = 158.65 ± 12.17 degrees) was similar to our study. Whereas, we found potentially substantial differences in the average values in the nasofrontal angles between our study (145 -149 degrees) and Ferdousi et al (130 -138 degrees) (26). In a sub-population of young Igbo adults, Loveday et al (7) showed significant gender differences in nasofrontal and cervicomental angles.…”
Section: Discussioncontrasting
confidence: 77%
“…In a facial profile study by Ferdousi AM, et al, on Bangladesh Christian Garo population, the angle of facial convexity was found to be higher in females (169.26° ± 4.43°) than males (158.65° ± 12.17°), similar to that in the North Indian population and White European population. The higher convexity in females could be explained by the fact that in general the facial contours of females were softer than those of males, especially in the area of the nose, lips and chin [26].…”
Section: Advances In Health Science Research Volumementioning
confidence: 99%